Mazax akephaloi sp. nov.—a new Neotropical spider species resembling ‘headless’ Ectatomma ants (Araneae: Corinnidae: Castianeirinae) - Perger, Robert; Pett, Brogan L. (Zootaxa, 2022)
A new ant-like spider species of the subfamily Castianeirinae, Mazax akephaloi sp. nov., representing the second species of Mazax recorded from South America, is described from the Bolivian orocline and the Paraguayan Chaco region. The new species superficially resembles Mazax ramirezi Rubio & Danişman, 2014, but can be distinguished from this species and all other congeners by a combination of the following characters: feathery setae on the carapace, a tibia I spine formula of 5–4 in males and 5–5 in females, the embolus sub-apical with a spatulate extension, the lung-shaped spermathecae II and slightly undulating copulatory ducts. Adults of M. akephaloi sp. nov. were observed foraging in association with workers of the ant Ectatomma permagnum Forel, 1908 on the ground or leaf litter along forest edges. Although the spiders were lacking a structure imitating the head of the ants, they shared several characters (dark brown integument with distinct, coarse wrinkles and shiny reflections, abdomen anteriorly with dorsally pointing process and distinct median constriction) that increased the species-specific similarity to their potential ant models.